Pro WPF in C# 2010: Windows Presentation Foundation in .NET 4.0 - MacDonald, Matthew (Apress, 2012)
This book is an in-depth exploration of WPF for professional developers who know the .NET platform,the C# language, and the Visual Studio development environment. Experience with previous versions of WPF is not required, although new features are highlighted with a “What’s New” box at the beginning of each chapter for more seasoned WPF developers.